KOMUNIKASI LINTAS BUDAYA DALAM MENJAGA KERUKUNAN ANTARA UMAT BERAGAMA DI KOTA TANJUNGBALAI - Kaya Arfah; M. Joharis; Muhammad Fharisi; Muhammad Ridha (Universitas Pahlawan Tuanku Tambusai, 2022)
Indonesia is a multicultural country that has many ethnicities and cultures. This makes Indonesia very vulnerable to inter-ethnic or inter-religious conflicts. To avoid this conflict, tolerance is needed in maintaining harmony between religious communities. One of the areas where there is conflict between religious communities in Tanjungbalai City, as a result of the problem of mosque loudspeakers (Toa) in the holy month of Ramadan. A resident who is a Buddhist, named Meliana who feels disturbed by the reading of the holy Qur'an at the time of tadarusan on the night of the holy month of Ramadan. The cause of conflict is due to poor communication between religious communities. In this case, the theory used in this research is the concept of cross-cultural communication and inter-cultural conflict by Samovar and Littlejohn & Domenici. Then also used the concept of social interaction from Gillin and Gillin. This research was conducted using a qualitative case study method and with the aim of looking for cross-cultural communication such as what happened between Muslims and Buddhists when the conflict occurred at that time. Based on this research, it was found that there was acculturation between Muslims and Buddhists. This acculturation indicates that the interaction formed between the two religious groups is an associative interaction pattern, so that there is no conflict as in other areas. Keywords: Communication, Cross Culture, Harmony, Religion